Imbalance of regulatory T cells and T helper type 17 cells in patients with chronic hepatitis C - Hao, Chunqiu (Immunology, 2014)
Pegylated interferon and ribavirin combination therapy is known to be effective in suppressing viral replication in 50–60% of hepatitis C virus (HCV) -infected patients. However, HCV-infected patients often exhibit varied responses to therapy. Therefore, the identification of immunological markers associated with the clinical outcomes of antiviral treatment is critical for improvement of therapeutic options. In this study, we aimed to investigate the ratio of CD4(+) CD25(+) FoxP3(+) regulatory T (Treg) cells to interleukin-17A (IL-17A) -producing T helper type 17 (Th17) cells, and its association with clinical outcomes in response to anti-HCV treatment. In all, 114 patients with HCV infection received pegylated interferon-α2a and ribavirin therapy for 48 weeks, and the frequency of Treg cells and Th17 cells as well as the levels of secreted cytokines were longitudinally analysed by flow cytometry and ELISA. Treg cell proportions and IL-10 production were significantly elevated in HCV-infected patients, especially for HCV genotype 1b. However, the frequency of Th17 cells as well as the secretion of IL-17, IL-22 and IL-23 did not reveal notable difference between HCV infections and healthy individuals. Inhibition of HCV replication was accompanied by a reduction in Treg cells, but little influence on Th17 cells, which led to a significant decrease in Treg : Th17 ratios. Skewed Treg : Th17 ratios existed in chronic hepatitis C. HCV RNA load is closely associated with Treg : Th17 ratios during pegylated interferon-α2a and ribavirin treatment in HCV-infected patients. The imbalance of Treg cells to Th17 cells might play an important role in persistent HCV infection.